Effects of increasing dietary lysine and energy levels on growth efficiency, nutrient absorption, and meat carcass traits in growing-finishing pigs - Sarbani Biswas; De Xin Dang; Sungbo Cho; Dae-Kyung Kang; In Ho Kim (Journal of Animal Science and Technology)
This study was executed to estimate the impacts of increasing dietary standardized ileal digestible (SID) lysine and net energy levels on growth, nutrient absorption, and meat carcass traits in growing-finishing pigs. In total, 90 pigs [(Yorkshire × Landrace) × Duroc] were erratically dispensed to 3 treatments (6 replicate/treatment) with 5 pigs (3 barrows and 2 gilts) per pen, and their average primary body weight was 20.51± 0.02 kg. The trial period was 16 weeks (growing stage, initial to week 8; finishing stage, week 8 to week 16). The dietary treatments used included control (CON) as the basal diet, TRT1 (basal diet + 0.05% SID lysine), and TRT2 (basal diet + 0.05% SID lysine + 0.084 MJ/kg net energy) for both the growing and finishing stages. Both the TRT1 and TRT2 group diets improved (p = 0.033) average daily gain (ADG) at week 12 and tended to enhance (p = 0.088) body weight at week 12 and ADG at the overall period compared to the CON group. Moreover, pigs in the TRT2 group had higher backfat thickness (p = 0.034) at week 12 in comparison to the TRT1 and CON diets. Nevertheless, no treatment effect was found (p > 0.05) in nutrient absorption or carcass grade among the dietary treatments. Hence, incorporating the increasing level of 0.05% SID lysine and 0.084 MJ/kg net energy into the pig diet during the growing and finishing stages can be considered a suitable approach for enhancing both growth efficiency and carcass backfat thickness in pigs.